Evaluation of a equipment for the mechanical obtaining of trace fiber from the golden pineapple harvest - Velásquez Ccosi, Percy Fermín (2020)
The research aims to design, build and evaluate a machine that has the ability to release cellulose from the rest of residual biomass and thus provide added value to the pineapple bark fiber. A theoretical study was carried out on the raw material and technology involved in obtaining cellulosic fiber, where it is potential material for the textile industry, tanning, paper pulp, etc. Therefore, the components of the prototype were designed, so it is necessary to analyze and determine the efforts to which they are subjected when the mechanical system (in which they are integrated) is under certain operating conditions. The characteristic of the design is that it has (02) very differentiated bodies: mobile and static, it is accurate in the load of the raw material and is clearly for batch type jobs and especially is unarmable in its components for maintenance